Temporal variability of the mass exchanges between the main inlet of Ria Formosa lagoon (southwestern Iberia) and the Atlantic Ocean. (15th November 2019) - Rosa, Alexandra; Cardeira, Sara; Pereira, Catarina; Rosa, Mónica; Madureira, Miguel; Rita, Filomena; Jacob, José; Cravo, Alexandra
Abstract: Understanding the mass exchange patterns between coastal lagoons and ocean plays a key role to explain their impact upon the water quality and biological productivity of these systems. Ria Formosa is a temperate lagoon on the southwestern coast of Iberia, one of the most important coastal system in this region in terms of biological productivity, ecological and economic values. Given its relevance and strong interconnectivity with the adjoining ocean, the quantification of these exchanges is a key issue that had not yet been thoroughly addressed. In this context, this study is focused on understanding the role of Ria Formosa's main inlet in terms of mass budgets dynamics of water, nutrients, suspended solids and chlorophyll a with the Atlantic Ocean and to identify its seasonal variability. In order to attain this purpose, the influence of the forcing mechanisms at different time scales, including tides, oceanographic/meteorological synoptic conditions and seasons, was assessed. To accomplish this, six semidiurnal tidal cycles surveys were conducted at Faro-Olhão inlet, comprising hourly water samples collection and in situ measurements at a selected cross-section of the inlet channel. Results revealed that mass exchanges variability through Faro-Olhão inlet was mainly due to oceanographic processes (upwelling and coastal countercurrent events) and, secondly, to phytoplankton activity within the lagoon. Seasonally, regardless the direction of the residual current through the inlet, Ria Formosa acted as a source of material during Spring and Summer seasons, which contributed to increase the biological productivity of the coastal ocean. Upwelling events that occurred more evidently during the Autumn survey drove an import amount of nutrients into the lagoon, enhancing its biological productivity. Furthermore, the rainfall period that prevailed before the Winter survey contributed to export material and nutrients to the adjacent ocean, confirming that Ria Formosa fertilizes the coastal ocean, even during a period of low productivity. Highlights: Driving mechanisms forcing the Ria Formosa-Atlantic Ocean exchanges were assessed. Net exchanges of the compounds did not follow the tidal rhythm of the water volume. Oceanographic and biological processes superimposed the tidal influence. Ria Formosa acted as source of nutrients and chlorophyll a during Spring and Summer. Ria Formosa acted as sink of nutrients and chlorophyll a during Autumn and Winter.